(untitled) (Latakia University Journal -Medical Sciences Series, 2019)
أظهرت هذه الدراسة التي أجريت على200 مريض سكري من النمط الثاني وجود علاقة ارتباط ايجابية بين فعالية غاما غلوتاميل ترانس ببتيداز المصلية GTγ ومستوى الشحوم الثلاثية في المصل، وكذلك بينGTγ ومشعر كتلة الجسم (BMI) وهذا يدل على وجود علاقة أيضا بين فعالية GTγ ومكونات المتلازمة الاستقلابية. بالإضافة لذلك كان هناك ارتفاع في مستوى الشحوم الثلاثية عند 55,5% من المرضى الذين تمت دراستهم. أما الكولسترول الكلي فإنه كان ضمن الحدود الطبيعية. وعند المرضى الذين ارتفع عندهم مستوى الكولسترول الكلي أكثر من 200 ملغ% فإنه كان هناك انخفاض في مستوى HDL وارتفاع مستوى LDL عند 55,9% و 93,2% من هؤلاء المرضى على التوالي. وهذا مايفسر وجود اضطراب في استقلاب الشحميات عند مرضى السكري والذي يؤهب بدوره لأمراض وعائية قلبية. This study which was carried out on 200 patients with diabetes type 2 has shown a positive association between serum gamma glutamyl transpeptidase ( γGT ) activity and serum levels of triglycerides, and also between γGT activity and body mass index (BMI), and this refers to a relation between γGT activity and the component of metabolic syndrome. There was an increased level of triglycerides in 55,5% of patients. On the other hand, the total cholesterol was within desirable limits. In addition to that, the levels of HDL cholesterol were low and the levels of LDL cholesterol were high in 55.9% and 93.2% of the patients who had cholesterol more than 200mg% respectively. This may explain that there is dyslipidemia in diabetes mellitus subjects which may lead to cardiovascular diseases.